The Jargon Used in Avengers: Endgame (2019) Movie: Sociolinguistics Study - Hevira Normayanti; Heri Heryono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and examine closely the form and the function of Avengers: Endgame (2019) movie. The purpose of the research was to describe the forms and functions of the movie Avengers: Endgame (2019). Jargon is a special vocabulary used in every area of life, skill, and environment.  A descriptive analysis method was used to carry out the research. The data used were taken from the Avengers: Endgame (2019) movie and the transcript from wiki. The results demonstrated that there are four forms of jargon, namely phrase (43.86%), word (35.09%), acronym (15.79%), and abbreviation (5.26%). Besides, there are three functions of jargon, 1) jargon gives a people a sense of belonging to a specific group of avengers, 2) jargon can also make it easier for a person to communicate with their friends/ groups of avengers, 3) jargon as effective signals for identification of communication with avengers.